2008
DOI: 10.1080/13811110701857491
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gatekeeper Training for Suicide Prevention in Veterans

Abstract: Clinical providers and "front line" nonclinical staff who work with veterans, families, and communities are natural gatekeepers to identify and to refer veterans at risk for suicide. A national cohort (n = 602) of community based counseling center staff from the U.S. Department of Veterans Affairs (VA) participated in an evaluation of a brief standardized gatekeeper training program and a scripted behavioral rehearsal practice session. A significant difference in knowledge and self efficacy was observed from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 12 publications
6
82
0
Order By: Relevance
“…Four of the five sections of the suicide and suicide prevention self-report survey instrument have been utilized in previous research (Matthieu et al, 2008, 2009). These sections include: (1) Organizational assessment, (2) Provider demographics, (3) Individual-level factors, (4) Exposure to suicide, and (5) Awareness of suicide prevention resources.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of the five sections of the suicide and suicide prevention self-report survey instrument have been utilized in previous research (Matthieu et al, 2008, 2009). These sections include: (1) Organizational assessment, (2) Provider demographics, (3) Individual-level factors, (4) Exposure to suicide, and (5) Awareness of suicide prevention resources.…”
Section: Methodsmentioning
confidence: 99%
“…A specific policy mandate of assessing suicide risk in mental health and non-mental health settings is mentioned in this report, as well as in the recent release of the National Strategy for Suicide Prevention (NSSP) (HHS, 2012). The providers working in these settings are the “front lines” of services provided to veterans and military families, and as such they serve a role as “gatekeepers” for at-risk veterans (Matthieu, Cross, Batres, Flora & Knox, 2008; Matthieu, Chen, Schohn, Lantinga, & Knox, 2009). Their perspectives are critically important in understanding how to tailor interventions aimed at increasing rates of referral for necessary, life-saving, crisis intervention services.…”
Section: Introductionmentioning
confidence: 99%
“…What follows are descriptions of the key findings and lessons learned from each of these enhanced program evaluations ("enhanced evaluations"), and the actionable knowledge framework used to make these findings relevant and actionable for use by practitioners in the field of suicide prevention. Prior research has shown that immediately after gatekeeper training, participants showed increased knowledge (actual and perceived), improved attitudes about suicide prevention, increased confidence (self-efficacy beliefs), and skills to help at-risk individuals [38][39][40][41][42]. Little research exists, however, on whether increases in gatekeepers' knowledge, attitudes, beliefs, and skills lead to actual gatekeeperhelping behaviors, nor is there much research on the long-term effectiveness of gatekeeper training in preventing suicidal behavior.…”
Section: Original Researchmentioning
confidence: 99%
“…Veteran's Administration counseling centers [17]. Based on survey data, researchers identified significant improvement from pre-post-training in knowledge and selfefficacy (p<0.0001) with greatest impact on knowing what to say and do.…”
Section: Nationwide Programsmentioning
confidence: 99%
“…Based on survey data, researchers identified significant improvement from pre-post-training in knowledge and selfefficacy (p<0.0001) with greatest impact on knowing what to say and do. Authors concluded the training was a promising intervention [17].…”
Section: Nationwide Programsmentioning
confidence: 99%